The Lancashire cotton industry and its rivals international competition in cotton goods in the late nineteenth century : Britain versus India, China, and Japan - Kawakatsu, Heita 1948-; LTCB International Library Trust; Kokusai Bunka Kaikan (Tokyo, Japan). (Tokyo International House of Japan, 2018)
The study based on his original research, undertaken in Oxford and subsequently in Japan, covers the important nexus established between Japan and the United Kingdom in the nineteenth century with the export of cotton textiles (of higher quality) from Britain to Asia. This historical link between key industries in our two countries is now happily mirrored in current scholarship, of which this is a prime example. It is no function of a brief preface to replicate the conclusions of detailed research but to emphansize the sider context of the research which lies behind the text of this book, which I am most happy to endorse. -- Jacket.
Types of raw cotton and their evolution. The eastward and westward spread of cotton cultivation -- The spread of cotton textiles to the West : India's role in the industrial revolution -- Specialisation in cotton goods in Far Eastern markets, 1870-1900. British expansion into Asian markets -- Comparison of prices between British and Japanese cotton cloths -- Quality differences between cotton goods -- Quality differences in raw cotton -- Conclusion -- Epilogue. Two modes of 'escape-from-Asia' -- Appendices. British exports of cotton goods to India, China, and Japan -- Imports of cotton yarn into British India, 1871-1910 -- The revision of the Japanese commercial tariff on cotton manufactures in 1866 -- Distribution of English shirtings and yarns to Japanese -- Dimensions of samples of Japanese cotton piece goods forwarded in the commercial report on the cotton trade and manufactures of Japan -- Competition in the Far Eastern yarn markets between Lancashire and Bombay cotton spinning industries -- Raw cotton imported into and exported from India.
"LTCB International Library Trust/International House of Japan."
Originally presented as the author's thesis (Ph. D.)--University of Oxford, 1985, under title: International competition in cotton goods in the late nineteenth century with special reference to Far Eastern markets.
Includes bibliographical references (pages 305-319) and index.
Keywords: Cotton textile industry; Cotton textile industry; Cotton trade; Cotton trade -- Great Britain; History